Steadfast ebook - Gray, Claudia (Spellcaster, 2014)
The second book in the dazzling Spellcaster series from New York Times bestselling author Claudia Gray is perfect for fans of the Beautiful Creatures and Hex Hall series. Nadia, Mateo, and Verlaine saved Captive's Sound from the dark Sorceress Elizabeth...or so they thought. Despite their best efforts, a greater evil has arisen, and its dark magic has begun to call Nadia. With her Steadfast, Mateo, and her best friend, Verlaine, Nadia must fight the black magic that tempts her, and stop the One Beneath before He comes to claim her power as His own.